2018
DOI: 10.1007/s10682-018-9940-9
|View full text |Cite|
|
Sign up to set email alerts
|

Male nutritional history affects female fecundity in a male-dimorphic mite: Evidence for a nuptial gift?

Abstract: In male-dimorphic species, males are often either armoured 'majors' that can monopolise access to females, or unarmoured and defenceless 'minors' that cannot. However, majors, unlike minors, have to spend energy to maintain their weaponry. Like-for-like, this could mean that minors have relatively more energy available to increase their reproductive output through e.g. sperm competition, or the transference of nutrients by means of a nuptial gift. Such a fitness advantage to minors could therefore contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 76 publications
0
10
1
Order By: Relevance
“…We did not find any effect of nutritional state on the reproductive output of males of different morphs, neither did we find that scramblers performed better than fighters under starved conditions. This does not support our hypothesis or the results obtained by Van den Beuken and Smallegange (), who, in a similar experiment, found that starved females mated to “fed” males produced more offspring than starved females mated to “starved” males. Importantly, after reaching maturity, “fed” males were fed for a single day and “starved” males were always starved in the study by Van den Beuken and Smallegange ().…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We did not find any effect of nutritional state on the reproductive output of males of different morphs, neither did we find that scramblers performed better than fighters under starved conditions. This does not support our hypothesis or the results obtained by Van den Beuken and Smallegange (), who, in a similar experiment, found that starved females mated to “fed” males produced more offspring than starved females mated to “starved” males. Importantly, after reaching maturity, “fed” males were fed for a single day and “starved” males were always starved in the study by Van den Beuken and Smallegange ().…”
Section: Discussioncontrasting
confidence: 99%
“…Females were measured only once, after mating. The mating period was set at 24 hr because (a) this should have been more than enough time to complete mating (and mate searching) (Radwan & Siva‐Jothy, ), (b) a previous study found that fighters often kill females if left without food for an extended period of time (Van den Beuken & Smallegange, ), and (c) we wanted to assess whether males, particularly starved males, died more often after mating, perhaps as a result of a terminal reproductive investment; however, no male died of such causes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, this was a demographic response if juvenile or adult females were killed more frequently by the larger number of fighters in fighter lines (cf. Van den Beuken and Smallegange 2018). The higher number of females likely yields a high clutch growth rate in growing populations (Lee et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These four stock cultures have been intermixed approximately every 6 months to reduce the level of inbreeding. In order to obtain virgin females to start the first generation, we collected 240 quiescent tritonymphs (moulting stage immediately preceding adulthood) from our four stock populations (60 from each) and stored each in 7-mL ‘individual tubes’ (50 × 16 mm) (the maintenance of the stock cultures is described in Van den Beuken and Smallegange 2018). Individual tubes were filled for about two-thirds with plaster of Paris, with charcoal for contrast.…”
Section: Methodsmentioning
confidence: 99%